Striking A Balance: Children’s Development Rights and the Halal Quandary in Childhood Vaccination - Iffad Afiq bin Adam; Nurul Hidayat Ab Rahman (Penerbit USIM, 2025)
International Halal Management Conference (IHMC) : “Empowering Halal Industry Towards Globalization” / Editor :-Farah Laili Muda @ Ismail, Nur Ainna Ramli & Anita Ismail Organized by Faculty of Economics & Muamalat, Universiti Sains Islam Malaysia 9 September 2025